1983
DOI: 10.1104/pp.71.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features Required for Inhibition of Soybean Lipoxygenase-2 by Propyl Gallate

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

1984
1984
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 15 publications
1
6
1
Order By: Relevance
“…These trends were much more obvious in the peroxidase assays (Figs. Consistent with this, we have demonstrated that n-propyl gallate inhibits lipoxygenase in vitro (data not shown) as previously reported by Peterman & Siedow [21]. Therefore, in the leaf protoplasts, at the time when lipoxygenase activity is rising and peroxidation is occurring, the enzymes responsible for removal of peroxides are decreasing.…”
Section: Discussionsupporting
confidence: 91%
“…These trends were much more obvious in the peroxidase assays (Figs. Consistent with this, we have demonstrated that n-propyl gallate inhibits lipoxygenase in vitro (data not shown) as previously reported by Peterman & Siedow [21]. Therefore, in the leaf protoplasts, at the time when lipoxygenase activity is rising and peroxidation is occurring, the enzymes responsible for removal of peroxides are decreasing.…”
Section: Discussionsupporting
confidence: 91%
“…At 24 h after onset of co-cultivation the proportion of rapidly dying infected cells was drastically reduced (40% less than the control without rc-propyl gallate) and formation of secondary fungal hyphae was enhanced 2-fold. Since salicylic acid has been suggested as an inhibitor of catalase (Chen et al, 1993;Sanchez-Casas and Klessig, 1994), whereas n-propyl gallate is a scavenger of reactive oxygen species and inhibitory to lipoxygenases (Peterman and Siedow, 1983), we investigated whether the level of intracellular reactive oxygen species is correlated with the rate of rapid cell death.…”
Section: Production Of Reactive Oxygen Speciesmentioning
confidence: 99%
“…Asterisks indicate significant difference from the untreated sample (Student's t test, *P < 0.05, **P < 0.01, ***P < 0.001). alternative oxidase enzyme, cyclooxygenases, and lipoxygenases (Peterman and Siedow, 1983). All of these enzymatic activities may produce ROS, including direct or indirect production of singlet oxygen.…”
mentioning
confidence: 99%